2019
DOI: 10.3390/ijerph17010027
|View full text |Cite
|
Sign up to set email alerts
|

Care Farming Program for Family Health: A Pilot Study with Mothers and Children

Abstract: We designed a pilot study to develop a family interaction model-integrated a care farming program with mother-child pairs as the participants. In this pilot study, we aimed to assess the effects of the care farming program on communication skills and psychological health in families. Sixteen mother-child pairs in Sejong, South Korea participated in this study. The families participated in a care farming program once a week for six weeks (90 min per session) between May and July 2018. The care farming program w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Our study adds to the literature on the role of TH in depression treatment by expanding to a severely affected inpatient population with MDD. Although earlier small group studies addressing a potential role for TH in depression treatment showed a positive trend towards improvement in overall clinical symptoms [34][35], a clear and significant effect of TH on clinical depression was not evident until structured studies addressing specific groups, such as geriatric patients and those with cognitive impairments, were conducted [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Our study adds to the literature on the role of TH in depression treatment by expanding to a severely affected inpatient population with MDD. Although earlier small group studies addressing a potential role for TH in depression treatment showed a positive trend towards improvement in overall clinical symptoms [34][35], a clear and significant effect of TH on clinical depression was not evident until structured studies addressing specific groups, such as geriatric patients and those with cognitive impairments, were conducted [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Now, scholars have begun to pay attention to the differences in subjective class identification. In the past, the subjects of the study have mainly been urban residents and migrant workers, and these studies have mainly explored the impact of a series of factors, such as life experience, administrative level, the father's professional reputation, and housing consumption, on class identification (Zhao and Ge, 2014;Wang, 2017;Rubin and Stuart, 2018;Reeves, 2019;Lee et al, 2020). Regarding the focus of the research, which is advocacy related to pursuing equality between men and women, the current research object is mainly female groups, the analysis of which may improve to a certain degree of research significance the understanding of the class identity of female groups (Bolzendahl and Myers, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Now, scholars have begun to pay attention to the differences in subjective class identification. In the past, the subjects of the study have mainly been urban residents and migrant workers, and these studies have mainly explored the impact of a series of factors, such as life experience, administrative level, the father's professional reputation, and housing consumption, on class identification (Zhao and Ge, 2014 ; Wang, 2017 ; Rubin and Stuart, 2018 ; Reeves, 2019 ; Lee et al, 2020 ). Regarding the focus of the research, which is advocacy related to pursuing equality between men and women, the current research object is mainly female groups, the analysis of which may improve to a certain degree of research significance the understanding of the class identity of female groups (Bolzendahl and Myers, 2004 ).…”
Section: Literature Reviewmentioning
confidence: 99%